The Taishōgoto: A Japanese Stringed Musical Instrument of Nagoya - Aaliyawani E., Sinin; Sinin, Hamdan; Ezra M., A. Duin; Khairul Anwar, Mohamad Said; Ahmad Faudzi, Musib (NC State University, 2025)
A taishōgoto is a Japanese instrument that combines a guitar and an autoharp with the scale buttons positioned in a piano-like pattern. Its unique design, which combines a strung zither body with a keyboard mechanism akin to a typewriter, makes it relatively easy to achieve precise pitch while generating a rich, bright timbre full of overtones. For open string, the gradient of the partials frequency versus the partials indicates the value of 100.95 (i.e., G2) is half the fundamental frequency i.e.,195 Hz (i.e. G3). For harmonicity (fn/f0) versus the partials number, the gradient of ~0.5 shows that the partials consist of the harmonic and in-harmonics partials. For fret 3, the gradient of the partials frequency versus the partials is 229.46 (i.e., A3#), equivalent to the fundamental frequency (f0) of 232 Hz (A3#). The taishogoto regardless finds practical applications in spite of these limitations. It has been evolved into a variety of genres, such as jazz, world, and folk music, and it continues to be of interest to experimental composers who are experimenting with its unique tonal characteristics. The taishogoto thus has a special place between usefulness and artistry, history and modernity, and innovation and limitation.